Direito do mar na constituição de 1988: o impacto das usinas nucleares no meio ambiente marinho - Ponsoni, Natalie Braz (2007)
In the First Chapter of this Master s Thesis is presented in general aspects the biological situation of the maritime ecosystem, taking into account its several composition. The next Chapter offers an explanation of the legal guardianship of those various resources living in the maritime ecosystem. Yet in the Third Chapter the environmental protection takes part in the situation of the Brazilian juridical structure, specially the Federal Constitution of 1988, major law of all juridical system. The last Chapter devotes itself to the study of the nuclear reactors and the impacts of its installations over the environment. Finally, in Conclusions some aspects are brought up assuring the unconstitutionality of the nuclear dream